The enlightened capitalists cautionary tales of business pioneers who tried to do well by doing good - O'Toole, James (Harper Business, an imprint of HarperCollins Publishers, 2019)
James O'Toole, an expert on ethical leadership, analyzes the complicated history of businesspeople who attempted to marry the pursuit of profits with virtuous organization practices. He tells the largely forgotten stories of men and women who adopted forward-thinking business practices designed to serve the needs of their employees, customers, communities, and the natural environment.